Critical thinking education in the portuguese higher education institutions: a systematic review of educational practices (Revista Lusófona de Educação, 2018)
Critical Thinking (CT) education has been a field of growing concern within the Portuguese Higher Education (HE) context, in an attempt to meet the labour market needs and the most demanding and complex societal challenges. However, there is a lack of systematic literature review studies characterizing the different CT educational practices adopted by faculty teachers. Thus, this review intends to understand to what extent the Portuguese teachers in HE have been developing CT skills and dispositions in their students, in a continuous, explicit and effective way. Following the steps of review methods, 27 empirical studies complying with the inclusion criteria were analysed. Results show that CT educational practices are gradually increasing over the years, but they tend to be developed with an implicit, non-intentional and short-term basis, neglecting the development of CT dispositions in the classroom. Studies from different nature are needed (experimental, longitudinal) in order to assess the permanency or generalization of CT in students. Several difficulties were found and future work should stimulate the discussion on the ways to overcome them, guiding HE teachers and institutions in the development, support and evaluation of CT practices.Keywords: higher education; critical thinking; educational practices; literature review